Postharvest responses of chokanan mango fruit to hot water dip treatment - M., Salumiah; Ding, Phebe (2007)
This study was conducted to determine physico-chemical changes in Chokanan mango fruits after hot water dip treatment at 26 and 55⁰C for 5,15 and 25 min. Chokanan mango fruits were obtained from pasar Borong Selangor at mature green stage (ripening stage RS) 1), the fruits were divided into 2 batches, the first batch of fruits were dipped in water of 26⁰C for 5.15 and 25 min while second batch of fruits were dipped in hot water of 55⁰C for 5,15 and 25 min. The dipped fruits were showered with water of 26⁰C for 20 min and then air dried and packed in cartons. Cartons containing the fruits and 0.02 mL/L acetylene were placed in a room of 26⁰C with relative humidity 75-80% for ripening. After 48 hours, the cover of the carton was opened and the fruits were allowed to ripen to RS 5. The fruits at RS 1.3 and 5 were analyzed for peel colour, flesh firmness, soluble solids concentration (SSC), ascorbic acid content (AA),pH titratable acidity (TA), disease incidence and heat induced injury. The experiment was conducted using a randomized complete block design with a factorial (2 dipping temperatures x 3 dipping times x 3 ripening stages) and 4 replications. The data were analyzed by using analysis of variance and differences within each factor were determined by LSD. The results indicated that, the peel color, flesh firmness, SSC,AA,pH,TA disease incidence and heat induced injury of Chokanan mango fruit were not affected by dipping temperature and time while the quality characteristic of the fruits was affected by ripening stage as fruit ripen. The interaction between dipping temperature x time did not show any significant effect on quality characteristic of Chokanan mango fruit.However, the interaction between dipping temperature x ripening stage affect diseaseincidence and heat induced injury. From the result of this study, HWD treatment can be used as a control method to postharvest disease incidence of the Chokanan mango fruits because the physic-chemical quality characteristics of the fruits was not affected. It is suggested that HWD treatment for 5 min is sufficient to control postharvest disease incidence and retain fruit quality caharacteristics of Chokanan mango fruits.